2021
DOI: 10.1016/j.ijcha.2020.100682
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of high sensitive troponin in predicting 30-day mortality among patients admitted to hospital with influenza

Abstract: Background Worldwide, seasonal influenza causes significant mortality and severe infections may cause cardiac injury. High-sensitive-troponins (hsTnT) are sensitive and specific markers of myocardial damage. This study investigated the prognostic impact of hsTnT on 30-day mortality in hospitalised influenza patients. Methods This retrospective study included influenza patients ≥ 18 years, who had hsTnT performed during admission in two tertiary-hospitals in South Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
5
1
2
Order By: Relevance
“…In this prospective cohort study assessing the prevalence and prognostic value of elevated hs-cTnI in an unselected population of patients with laboratory-confirmed influenza infection patients were included during three influenza seasons. The prevalence of elevated hs-cTnI in our cohort of 181 patients with documented influenza was 6%, much lower than in two recent retrospective studies, which found that the prevalence rates of elevated hs-cTn in patients with influenza were 31.8, 23 47.7, 25 and 65.5%. 24 However, unlike the present prospective study, the two previous retrospective reports calculated the prevalence of elevated hs-cTn in selected individuals in whom hs-cTn had been measured, thus increasing the likelihood of inclusion bias.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In this prospective cohort study assessing the prevalence and prognostic value of elevated hs-cTnI in an unselected population of patients with laboratory-confirmed influenza infection patients were included during three influenza seasons. The prevalence of elevated hs-cTnI in our cohort of 181 patients with documented influenza was 6%, much lower than in two recent retrospective studies, which found that the prevalence rates of elevated hs-cTn in patients with influenza were 31.8, 23 47.7, 25 and 65.5%. 24 However, unlike the present prospective study, the two previous retrospective reports calculated the prevalence of elevated hs-cTn in selected individuals in whom hs-cTn had been measured, thus increasing the likelihood of inclusion bias.…”
Section: Discussioncontrasting
confidence: 80%
“…By contrast, the median age of the patients in the previous studies was between 66 and 80 years, and a large proportion of patients had been admitted to hospital, implying more severe disease. 24 , 25 Additionally, in the recent prospective study 12.4% were admitted to the intensive care unit. 24 The prevalence rates of elevated hs-cTn patients aged ≥65 years in those admitted to hospital in the present study, however, were 10 and 14%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in addition to their reflection of cardiac injury, troponin levels were also reported to be of prognostic relevance in the presence of sepsis ( 28 – 30 ). Additionally, recent studies demonstrated an increased risk for cardiac complications and fatal outcomes in the presence of elevated troponin levels in influenza patients, with a significant impact on 30-day mortality rates ( 31 , 32 ). In the present study, a significant difference in troponin levels was already evident at the first day after admittance to ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Клиническое течение ОКС Наряду с COVID-19 приводимые в литературе данные исследований течения вирусных инфекций прошлых лет подтверждают высокие риски ССО. Так, вирус гриппа значительно увеличивал риски развития ОКС и внезапной сердечной смерти как в раннем, так и в отсроченном периоде течения болезни [39][40][41]. Результаты исследования 133562 случаев ИМ в период эпидемии сезонным гриппом показали более высокую частоту ИМ в периоды с наибольшим количеством зарегистрированных случаев гриппа.…”
Section: респираторный синдромunclassified